The role of the discipline «Foreign language» in education of students in the spirit of national idea «Мәнгілік ел» (Eurasian Journal of Philology Science and Education, 2016)
The paper considers the proper usе of educational potential of English classes in educating students in the spirit of the national idea of «Мәнгілік ел». The aim and tasks of teaching the discipline «Foreign language» are directed towards not only foreign language acquisition but also they have the function to train the specialists of a new type. The paper reports that within the framework of education in the spirit of the national idea «Мәнгілік ел» teachers of the English language at Al-Faraby Kazakh National University conduct different kinds of cultural events. They are the implementation of the project «Brighten the corner where you are» the aim of which is to instill the spirit of patriotism, love for motherland, language, national traditions and customs.
Keywords: National idea; project; value; higher educational institu¬tions; spirit; moral norms.